O plano real e a armadilha macroeconômica - D’Almeida, Alexandre Rodrigues (1999)
In the 1970s, with the end of the gold-dollar standard and the adoption of exchange rates and floating interest rates, the question of the possibility of abrupt and unexpected adjustments is explicit. in exchange. In the early 1980s, the policy adopted by the United States was that of the strong dollar, which worked with an overvaluation of the currency and high interest rates, a strategy that caused an unprecedented liquidity crisis in international capital markets. Rising interest rates have put the burden of adjustment on borrowers - especially for Latin American countries. Consequently, in view of the payment difficulties that were established, impacts on credit banks that had advanced resources through syndicated loans were generated. Following the perspective of solving the debt debts of the debtor countries, the IMF's adjustment policies advocated the generation of trade surpluses to repay debt service, which turned these countries into net exporters of real resources, to the detriment of growth of the internal market. From the second half of the 1980s onwards, the devaluation of the dollar (weak dollar policy), coupled with new financial mechanisms that involved hedging schemes, as well as the emergence of institutional investors as major liquidity holders, created a different situation. These factors, combined with market deregulation processes and the interrelationship between credit and capital markets, have generated excess liquidity in search of appreciation. In this configuration, the adjustment policy indicated for Latin American countries began to prescribe the need to absorb external resources with high arbitrage rates, which made these countries absorbers of financial capital. In this context, Latin America's adjustment policies were articulated, especially linked to the prescription of the so-called “Washington Consensus”.